Faktor-Faktor Yang Mempengaruhi Wajib Pajak OrangPribadi Dalam Pemenuhan Kewajiban Perpajakannya(Studi Empiris Pada Wajib Pajak Orang Pribadi Yang Terdaftar Di KantorPelayanan Pajak Pratama Surakarta & Sukoharjo) - Nurinasari, Dian; , Drs. Muhammad Abdul Aris, M.Si (2016)
The purpose of this study was to examine whether the taxpayer awareness, pengetahuan and understanding of tax laws, a good perception on the effectiveness of the tax system and service quality has a significant influence on the consciousness of paying taxes.The population in this study is the taxpayer who is listed on KPP Pratama Surakarta and Sukoharjo. The sampling technique uses accidental sampling. The sample in this study were taken using the formula slovin. The research data is primary. The number of samples in this study were 100 taxpayers. Methods of data analysis used in this research is multiple linear regression analysis. The results of this study indicate taxpayer awareness, knowledge and understanding of tax laws, a good perception on the effectiveness of the tax system, the quality of service have positive influence on the willingness to pay taxes. T test result showed that the level of understanding of the taxpayer, the quality of service tax authorities, tax penalties and taxpayers environmentally positive effect on the level of compliance of individual taxpayers. The results showed that R2 values obtained 0.454 which means that 45.4% are influenced by the willingness to pay taxes taxpayer awareness, knowledge and understanding of tax laws, a good perception on the tax system and the quality of service tax authorities. The remaining 54.6% influenced by variables outside the model. T test results showed that the influence taxpayer awareness, knowledge and understanding of tax laws, a good perception on the tax system and the quality of service fiskus positive influence on the willingness to pay taxes.